The Effects of Trademark Rights on the East African Common Market Concocting an Appropriate East African Community Trade Mark Model based on the European Trade Mark System - Jaconiah, Niteleka Jacob Nichaenzi (Munich Intellectual Property Law Center - MIPLC, 2012)
Trademark rights play a significant role in the proper functioning of a common market of a given regional bloc. Experience teaches that, unless national trade mark regimes of individual countries cooperating in a given regional bloc such as the East African Community (EAC) are integrated into a common market, trademark proprietors may invoke their intellectual property rights to dissect the common market into different national markets and in that way blocking the free movement of trademarked goods from one part of the common market to the other. This book is therefore intended as guideline when addressing the challenges posed on a regional common market by the absence of a common market for trademarked goods. The study provides for legal techniques through which the latter market may be established to compliment an existing common market as a policy choice in favour of the principle of free movement of goods. To this end, the book analyses key principles that govern the EU's community trade mark system and determines the extent to which these principles may be adapted to suit the EAC common market.